Report of the National Executive Committee to the 40th annual conference to be held in The Central Hall, Westminster, June 2nd, 3rd an 4th, 1941. - Labour Party (London : Labour Party, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; Groot-Brittannië.